Experimental study on asynchronous construction for composite bridges with corrugated steel webs. (June 2019) - Deng, Wenqin; Liu, Duo; Xiong, Yingqian; Zhang, Jiandong
Abstract: Asynchronous construction is a new construction method for composite girder bridges with corrugated steel webs. This new construction technology has multiple advantages over conventional cantilever construction technology, including a simple basket structure, low steel consumption, high material utilization, short construction period and superior stability. Herein, a 1:1 full-scale corrugated steel web model test is designed based on the Fenghua River Bridge, which is the longest span composite girder bridge with corrugated steel webs in China. This test analyzes the shear stress distribution of corrugated steel webs under the most unfavorable stress conditions and the ultimate bearing capacity of single corrugated steel webs under the most unfavorable load conditions during asynchronous construction. The deformation and stress conditions are measured to identify critical stress areas during construction. Additionally, the safety of each area during construction is verified to provide guidance for asynchronous construction plans for the same type of bridge structures. Highlights: A 1:1 full-scale test of a composite bridge with corrugated steel webs during asynchronous construction was performed. The vertical deflection difference between adjacent sections should be considered to control the linear of the main girder. A temporary horizontal support should be added to the corrugated steel webs to prevent the lateral deformation of the web. The corrugated steel webs have sufficient safety factor during asynchronous construction. The flange steel plates under loading points should be reinforced To prevent buckling.